Priorização dos itens sujeitos à manutenção preventiva em um equipamento do sistema elétrico de potência por meio da Análise Relacional Grey - Nagaki, Lincoln (2019)
This study was designed to improve the occurrence rates involving electric passenger transport systems on rails. Many of these occurrences end up partially paralyzing the system, causing great inconvenience to those who depend on this type of modal to get around. Conducting a survey of the failures that occurred for a period of approximately three years in the power substations of the system under study, it was found that the largest number of failures pointed to the high voltage circuit breakers that were mostly sporadic gas leaks. Some devices use vacuum caps for this purpose, but are limited for some high power applications. As these types of occurrences depend little on maintenance teams for prevention and correction, and most of the times do not influence the operating system due to its duality of equipment, it was chosen the second system that presented the most failures in this period, which are the feeder circuit breakers (feeders), which are responsible for the protection and safe isolation of electrical circuits whenever necessary. With data obtained by industry professionals, the most critical equipment in relation to the number of failures presented was verified. In another consultation, the risk perception spreadsheet was obtained, obtaining the Risk Priority Number, comparing it with the results obtained by applying the Gray Relational Analysis, inserting some weights in the occurrence, detection and severity indices suggested by some authors, where it was again analyzed for verification and validation of the obtained results, presenting an opinion of the professionals of the area to attest the results. Analyzing the results obtained by the Gray Relational Analysis it was found that this theory presented data consistent with reality, resembling those obtained by the traditional Failure Mode and Effects Analysis, providing a finer adjustment for maintenance planning, given the possibility insert the appropriate proportions of the indices in its entry.